Melting Curve Analysis of SNPs (McSNP®): A Gel-Free and Inexpensive Approach for SNP Genotyping. (February 2001) - Akey, J.M.; Sosnoski, D.; Parra, E.; Dios, S.; Hiester, K.; Su, B.; Bonilla, C.; Jin, L.; Shriver, M.D.
High-throughput methods for assaying DNA variation require two important steps: (i) discriminating the variation and (ii) de-tecting the signal. In this report, we describe a novel SNP genotyping method that we refer to as melting curve analysis of SNPs (McSNP ® ). McSNP combines a classic approach for discriminating alleles, restriction enzyme digestion, with a more recent method for detecting DNA fragments, melting curve analysis. Melting curve analysis is performed by slowly heating DNA fragments in the presence of the dsDNA-specific fluorescent dye SYBR ® Green I. As the sample is heated, fluorescence rapidly decreases when the melting temperature of a particular fragment is reached. We show that it is possible to determine the composition of simple mixtures of DNA fragments, such as those that result from restriction enzyme digestions of short PCR products. McSNP is well suited for high-throughput genotyping because 96 samples can be analyzed and automatically scored in 20 min. Our results clearly demonstrate that McSNP is a simple, inexpensive, and accurate means of genotyping SNP variation.